Five Cases of Recurrent Meningitis Associated with Chronic Strongyloidiasis - Shimasaki, Teppei (Am J Trop Med Hyg, 2015)
Although meningitis secondary to chronic strongyloidiasis is a rare complication, it is associated with a high mortality rate. Recurrent meningitis can occur if the underlying parasitic infection is left untreated. We report five cases of recurrent meningitis related to chronic strongyloidiasis that were associated with human T-lymphotropic virus type 1 (HTLV-1) infection. Common causative organisms are Escherichia coli, Streptococcus bovis, and Klebsiella pneumonia. One patient died during the second episode of meningitis. Three patients showed significant gastrointestinal and respiratory symptoms before developing headache and fever. In four cases, patients developed multiple recurrences even with the treatment of thiabendazol. Ivermectin seems to be a better agent compared with thiabendazol to achieve eradication of strongyloidiasis.